The Boomerang Thigh Flap: Optimizing the Donor Site for an Extended Skin Island Flap - Barreiro, Guilherme C.; Fioravanti, Alex B.; Borges, Luiz H. S.; Snider, Chelsea C. (Journal of Reconstructive Microsurgery, 2018)
Background The anterolateral region of the thigh is one of the most used donor areas for flaps. However, there are cases in which large defects require more than the conventional skin island provided by the anterolateral thigh flap (ALT). For an extended skin island flap, we developed a new boomerang thigh flap (BTF), in which a boomerang design includes perforators from multiple branches of the lateral circumflex femoral artery (LCFA), providing a single-pedicle, large, reproducible, and reliable flap. We report the anatomical study and the use of the new BTF in a clinical series.Methods We dissected 20 flaps in fresh cadavers to determine the anatomical landmarks, vascular pedicle pattern, perforator distribution, and BTF flap dissection technique. After achieving a reproducible and reliable technique, with primary closure of the donor site based on the pinch test, the BTF was applied for microsurgical reconstructions in the head and neck, lower limb, and upper limb regions.Results The BTF corresponds to a 45° confluence of the ALT and the tensor fascia lata (TFL) elliptical skin islands. It includes the perforators from the transverse/ascending and the descending branches of the LCFA , which conjoined into a single arterial LCFA pedicle in 85% (17) of the cadaver dissections. All the venous branches drained into a single lateral circumflex femoral vein. ALT perforator distribution followed literature descriptions, while TFL perforators were mainly septocutaneous and projected into a virtual rectangle of 6 × 4 cm at the lateral margin of the TFL. Average BTF dimensions were 40 × 8.6 cm. For the clinical cases, flap dimensions and pedicle characteristics were equivalent to the anatomical findings. The BTF was separated into two skin islands in four cases and no major complications were reported.Conclusion The BTF is a reliable, reproducible, and divisible flap that provides extended skin island for reconstruction of large defects.
Keywords: boomerang thigh flap; extended skin island; single-pedicle flap